Feelings of being a second victim among Spanish midwives and obstetricians - Irene Santana‐Domínguez; Héctor González‐De La Torre; José Verdú‐Soriano; Miriam Berenguer‐Pérez; Juan José Suárez‐Sánchez; Alicia Martín‐Martínez (Nursing Open, 2022)
Abstract Aim The aim of this study was to determine the prevalence of feelings of being a second victim among midwives and obstetricians in Spain and to explore possible differences between the two professions. Design Cross‐sectional descriptive‐analytical observational study. Methods An online survey collecting several variables was administered throughout the Spanish territory. Spanish version of the Second Victim Experience and Support Tool (SVEST) was used. The data collection period was from May to December 2020. Results A total sample of 719 obstetricians and midwives were studied. There were significant differences between the two groups with respect to seven dimensions of SVEST: greater feelings of being a second victim among obstetricians in the dimensions physical distress/p ≤ .001, non‐work‐related support/p ≤ .001 and absenteeism/p ≤ .001 and greater feelings of being a second victim among midwives in the dimensions psychological distress/p ≤ .001, supervisor support/p = .011, professional self‐efficacy/p ≤ .001 and intention to change jobs/p ≤ .001.